Modification of Early Response of Vitis vinifera to Pathogens Relating to Esca Disease and Biocontrol Agent Vintec® Revealed By Untargeted Metabolomics on Woody Tissues - Chervin, Justine; Romeo-Oliván, Ana; Fournier, Sylvie; Puech-Pages, Virginie; Dumas, Bernard; Jacques, Alban; Marti, Guillaume (Frontiers in Microbiology, 2022)
Esca disease is one of the most destructive grapevine trunk diseases. Phaeoacremonium minimum and Phaeomoniella chlamydospora are two of the known fungal pathogens associated with this disease. Today, biocontrol agents against Esca are mainly based on the use of the strain of the mycoparasite fungal genus Trichoderma such as the Vintec® product. The aim of this study was to investigate early response of woody tissues to Esca pathogens and identify metabolites that could be correlated with a biocontrol activity within a complex woody matrix. An untargeted liquid chromatography–high-resolution mass spectrometry metabolomic approach coupled to a spectral similarity network was used to highlight clusters of compounds associated with the plant response to pathogens and biocontrol. Dereplication highlighted the possible role of glycerophospholipids and polyphenol compounds, the latest mainly belonging to stilbenoids. Antifungal activity of some relevant biomarkers, evaluated in vitro on Phaeomoniella chlamydospora and Botrytis cinerea, suggests that some of these compounds can play a role to limit the development of Esca pathogens in planta.